قراءة في كتاب قصيدة النثر وإنتاج الدلالة أنسي الحاج أنموذجاً - برهم, لطفية; جابر, يوسف; المغرقوني, ليلى (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هذا البحث محاولة لتقديم قراءة أخرى لبعض القصائد النثرية, التي تم تناولها بالتحليل في دراسة الدكتور "عبد الكريم حسن" (قصيدة النثر وإنتاج الدلالة)؛ بغية توسيع أفق الدلالة بالنظر إلى موقع كل مفردة داخل سياقها وعلاقاتها النحوية مع غيرها. كما يهتم البحث بمناقشة القضايا الإشكالية المثارة على نحو علاقة التركيب والدلالة, والإيقاع الداخلي الذي يرد في الدراسة تحت اسم الإيقاع الخفي. This research tries to offer another reading of some prose poems that are written by "Unsy _ Alhag", and criticized by Producing Meaning ). The research aims at widening the meaning by searching for grammatical relations of words in comparison with its place in its context. This research deals with some important matter in the criticism, like the relationship between grammar and meaning, and internal rhythm, which is named in the basic study by The Hidden rhythm.